2014
DOI: 10.1590/0100-2945-379/13
|View full text |Cite
|
Sign up to set email alerts
|

Características agronômicas e ocorrência de mal-do-panamá em bananeiras tipo Pacovan

Abstract: Este trabalho objetivou avaliar características vegetativas, de rendimento e incidência de maldo-panamá na 'Pacovan', em dois ciclos de produção, nos híbridos 'Japira', 'Pacovan-Ken', 'Preciosa' e 'Garantida', recomendados para produtores pela Embrapa Mandioca e Fruticultura, e no 'PV79-34', em seleção. Utilizou-se o delineamento experimental inteiramente casualizado, com seis tratamentos e cinco repetições. Os dados foram submetidos à análise de variância, e as médias, agrupadas pelo critério de Scott-Knott (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
3
2
0
1
Order By: Relevance
“…Among banana plants with 'Pacovan'-type fruits, the most productive is 'PV79-34'; however, it is susceptible to Panama disease (RODRIGUES FILHO et al, 2014), as verified in the present study.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Among banana plants with 'Pacovan'-type fruits, the most productive is 'PV79-34'; however, it is susceptible to Panama disease (RODRIGUES FILHO et al, 2014), as verified in the present study.…”
Section: Resultssupporting
confidence: 83%
“…In all cycles, the lowest performance was observed for Caipira cultivar, similar to that observed by Camolesi et al (2012). As in the present study, Azevedo et al (2010) observed that 'PV79-34', a Pacovan-type hybrid susceptible to Panama disease (RODRIGUES FILHO et al, 2014), expresses greater vigor and smaller size than 'Pacovan' and its hybrids 'Preciosa', 'Garantida', 'Japira' and 'Pacovan-Ken'. Possibly, its male genitor identified as 79 (AA) provides the greatest vigor and smallest size (AZEVEDO et al, 2010), but it does not provide resistance to Panama disease as M53 to its progeny (RODRIGUES FILHO et al, 2014).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the first production cycle, highlighted by the largest number, Thap Maeo, PA94-0, FHIA 23, YB42-17, FHIA 02 and Caipira; in the second cycle, Thap Maeo, and in the third cycle, Thap Maeo. It was observed an increase in the total number of fruits in the first two cycles (without statistical differences between them) for the third cycle in the genotypes YB42-17 and Caipira, as well as from the first to second and third cycles (without statistical differences between the last two) regarding the YB42-47, Maravilha,Thap Maeo, Despite the differences detected between genotypes and cycles, comparing the results of this study with other, between the same cultivars, one can notice that the total number of fruits are inferior in this study (Nomura et al, 2013b;Silva et al, 2013b;Ribeiro et al 2013;Rodrigues Filho et al, 2014;Roque et al, 2014;Silva et al, 2016;Silva et al, 2017). Thus, two hypotheses could explain this discrepancy, 1 st ) cultivars are not adapted to the conditions of Rio Branco or; 2 nd ) the management dispensed to the orchard was not enough for the genotypes to express a greater quantity of fruit.…”
Section: Number Of Handsmentioning
confidence: 41%
“…Apesar da aceitação por parte dos consumidores a 'Pacovan' apresenta características indesejáveis como porte elevado, susceptibilidade às sigatokas-amarela e negra, características que podem onerar o custo de produção (Rodrigues Filho et al, 2014). Assim, o híbrido tetraploide 'BRS Vitória', por ser resistente à antracnose em pós colheita e às sigatokas, além de excelente qualidade dos frutos, pode ser uma alternativa aos cultivares do subgrupo Prata.…”
Section: Introductionunclassified